2015
DOI: 10.1111/bjd.13599
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of glomerulonephritis and chronic kidney disease in relation to the severity of psoriasis, concomitant medication, and comorbidity: a nationwide population-based cohort study

Abstract: Psoriasis was associated with a higher risk of developing CKD and GN. High severity, psoriatic arthritis involvement and concomitant NSAIDs use further increased the risk of CKD in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 48 publications
(186 reference statements)
0
95
1
7
Order By: Relevance
“…However, the reliability and validity of using these methods for grouping severe psoriasis and PSA has been demonstrated in previous studies and verified through sensitivity analyses. 3,4,47 Nevertheless, systemic treatment, rather than severe psoriasis itself may affect the outcomes. Systemic antipsoriatic treatment in patients with psoriasis may reduce cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reliability and validity of using these methods for grouping severe psoriasis and PSA has been demonstrated in previous studies and verified through sensitivity analyses. 3,4,47 Nevertheless, systemic treatment, rather than severe psoriasis itself may affect the outcomes. Systemic antipsoriatic treatment in patients with psoriasis may reduce cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Psoriasis has been associated with increased prevalence of cardiovascular risk factors, including hypertension, diabetes mellitus, and dyslipidemia. [3][4][5] Recent studies also indicate that patients with severe psoriasis have higher mortality, mainly because of higher risk of cardiovascular death (hazard ratio [HR] 1.57; 95% confidence interval [CI] 1. 26-1.96).…”
mentioning
confidence: 99%
“…In the time since our study was published, a few other papers have also reported an increased risk of CKD and ESRD among patients with severe psoriasis, 6,7 and an increased risk of death from renal disease among patients with psoriasis. 8 …”
Section: External Validitymentioning
confidence: 53%
“…Psoriasis has been found to be associated with diabetes, metabolic syndromes, CKD, cardiovascular disease and COPD in previous studies . Immune‐mediated processes are believed to play a role in these associations.…”
Section: Discussionmentioning
confidence: 87%